Directions for Improving Labor Force Surveys in Uzbekistan Based on Foreign Experience - A. T. Tairova (Статистика и экономика)
Purpose of the study. Studying international experience in the field of conducting Labor Force Surveys, comparing it and developing recommendations and proposals for improving methods of conducting Labor Force Surveys in the Republic of Uzbekistan.Materials and methods. The research methodology consists of a comprehensive analysis of the methodological provisions of some countries for conducting a Labor Force Survey, summarizing the key points arising from the analysis of literature on the topic, grouping them, comparing the methods of conducting a Labor Force Survey in some countries, the responsible departments, sampling methods and its size, the population being surveyed, etc.A graphical analysis of key statistical data obtained from the labor force survey was also carried out.Results. Based on the results of the study, a comparative table was compiled containing basic information about methods of conducting a Labor Force Survey in some countries. A graph has been compiled reflecting the situation with the employment and unemployment rates in the countries studied. Conclusions and proposals are also given for improving the methods of conducting a Labor Force Survey in the Republic of Uzbekistan, including the organization of a population census, the creation of a unified housing register and a population register, and the transition to a mixed collection of information using the CAPI-CATI method.Conclusion. The Labor Force Survey is recognized by countries as an important source of labor data. At the same time, approaches to forming a sample of households to be included in the survey are carried out differently in different countries. Most countries use the CAPI interviewing method, in which the respondent or interviewer uses an electronic device to answer questions, usually a tablet. The quality of the generated indicators, and therefore the effectiveness of government measures taken to support employment and reduce tensions in the labor market, depends on the quality of the Labor Force Survey. In this regard, proposals for improving the way Labor Force Surveys are conducted may be applicable in the Republic of Uzbekistan and improve the country's ranking in the Statistical Capacity Index.